Fontane in the twenty-first century - Lyon, John B., 1966-; Tucker, Brian, 1976-; Berman, Russell A., 1950- (Studies in German literature, linguistics, and culture., 2019)
"Theodor Fontane remains a canonical figure in German literature, the most important representative of poetic realism, and likely the best German-language novelist between Goethe and Mann, yet scholarly attention to his works often lags behind his stature, at least in the English-speaking academy. This volume, coinciding with Fontane's 200th birthday in 2019, assesses the relevance of his works for us today and also draws attention to the most current English-language research. Much has changed in the last two decades in critical theory, and the volume highlights how new methodological approaches and new archival research can update our understanding of Fontane's works. Although his novels are famously rooted in the details of quotidian life in nineteenth-century Germany, they also reflect larger historical transformations that resonate with our world today (e.g., financial crisis, class conflict, changing gender roles, and migration) and so speak to contemporary critical interests. The volume's contributors draw on literary and cultural studies approaches including gender and sexuality studies, emotion studies, transnationalism and globalization, media and visual studies, rhetorical criticism, paratextual criticism, and digital humanities. Their contributions survey a wide range of Fontane's literary production in order to speak to both German and non-German audiences in the twenty-first century"--